The Right Man for the Job - Coen N. Teulings; Pieter A. Gautier (Tinbergen Institute, 2000)
This paper describes a search model with a continuum of worker and job types, free entry and transferable utility. We apply a second-order Taylor expansion to characterize the equilibrium, derive the cost of search and show that it is decreasing in the substitutability of worker types. This cost of search is then decomposed into three components: unemployment, vacancy costs and mismatch. Our contact technology rules out congestion effects between different worker types and therefore exhibits increasing returns to scale. One third of those increasing returns in contacts are shown to be absorbed by firms and workers being more choosy. The resulting equilibrium is not efficient. Unemployment benefits can reduce the loss by serving as a search subsidy. Numerical simulations of the model show that our Taylor expansions are quite accurate.
Keywords: 330; Employment; Employee Selection; Unemployment; Employees; Labor; Arbeitsuche; Personalbeschaffung; Arbeitsvermittlung; Skalenertrag; Theorie